Digital rupiah: Are Indonesians ready? - Widodo, Kharisma Dwi; Juanda, Bambang; Setyowawan, Dwi; Lutfiyah, Dinda (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
Bank Indonesia has attempted to calibrate its policy approach to adopting a Central Bank Digital Currency (CBDC) called Rupiah Digital through the Garuda project, as an effort to address the issue of shadow banking that has developed into a shadow currency issue and even a shadow central banking issue. This study aims to determine the characteristics of digital banking users in Indonesia regarding the use of Central Bank Digital Currency (CBDC). This study was examined using panel data regression analysis and then confirmed using Structural Equation Model-Partial Least Structural (SEM-PLS) analysis. The results show that socioeconomics (digital use), digital literacy, digital access, and digital security influence CBDC implementation in Indonesia. Furthermore, Indonesian society is ready to accept and use CBDC (r-CBDC). However, the implementation must be gradual because socioeconomics (digital use), digital literacy, digital access, and digital security in Indonesia are not evenly distributed and are still centered on the island of Java.